Monito-Ring: An original fiber optic system for morphing application. (December 2015) - Ciminello, Monica; Bettini, Paolo; Ameduri, Salvatore; Guerreschi, Erika; Concilio, Antonio; Sala, Giuseppe
An original Monito-Ring system based on chirped fiber optic and draw tower grating array is presented. The target of this research activity is the realization of a device able to measure deformations of morphing structures which may show large, global displacements due to nonstandard architectures and materials adopted. The occurring strain field results, in turns, much more than the standard sensors can handle. Modulations are then necessary to keep the measured strain low. The proposed solution was conceived to overcome this limitation assuring a suitable reduction of the revealed strain. The concept is made of a flexible ring pinned on a certain number of points to the structural component of interest. The fiber optic is integrated within the ring, and depending on the angular position of the sensor, the ratio between the diameter elongation (i.e. structural strain) and the measured deformation (strain) can be almost arbitrarily set in a large range of values. From each spectrum provided by draw tower grating array, the corresponding unknown strain field is retrieved by applying an inverse technique obtaining an accurate continuous strain map. This article deals with a proof of concept analytical study first and then numerical and experimental validation.